PENGARUH PROFITABILITAS, LEVERAGE, SIZE DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 â 2013 - Jayanti Liliani, 12.05.51.0087; Parmono Hadi, Teguh (Students Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of profitability (ROE), leverage (DER), firm size (Size) and liquidity (Cash Ratio) to the Dividend Policy (DPR). The research was conducted on an industrial manufacturing company that listed on the Indonesian Stock Exchange. The research was conducted using secondary data. The sampling method in this study using purposive sampling method with the study period of 2010 to 2013. The data used in this research is data from manufacturing companies that meet the selection criteria. The analytical method used in this study is multiple regression analysis.The multiple regression shows that ROE and DER have negative and significant impact on DPR, Size has positive and significant effect on DPR, while Cash Ratio has negative and not significant effect on DPR. Adjusted R Square is 0,091 this means 9,1% of the dependent variable can be explained by the independent variable, while the remaining 90.9% is explained by other causes outside the model. Keywords: Dividend Payout Ratio, Return On Equity, Debt to Equity Ratio, Firm Size, and Cash Ratio